2013
DOI: 10.1016/j.anbehav.2012.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Bigger is better: honeybee colonies as distributed information-gathering systems

Abstract: In collectively foraging groups, communication about food resources can play an important role in the organization of the group’s activity. For example, the honeybee dance communication system allows colonies to selectively allocate foragers among different floral resources according to their quality. Because larger groups can potentially collect more information than smaller groups, they might benefit more from communication because it allows them to integrate and use that information to coordinate forager ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…Therefore, a foraging community might be necessary for Cape Gannets, and given that using cues from conspecifics reduces the time to get to foraging patches, we suspect that the large-scale density of potential cues is fundamental in determining the foraging efficiency of individuals. Individual fitness would partly depend on the community of predators, such that a large colony would allow for better foraging efficiency of its members, as has been found recently in honeybees (Apis mellifera; Donaldson-Matasci et al 2013). Consequently, a tradeoff can be expected between intraspecific competition (Ashmole 1963, Furness andBirkhead 1984, Lewis et al 2001) and foraging facilitation in colonial seabirds.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a foraging community might be necessary for Cape Gannets, and given that using cues from conspecifics reduces the time to get to foraging patches, we suspect that the large-scale density of potential cues is fundamental in determining the foraging efficiency of individuals. Individual fitness would partly depend on the community of predators, such that a large colony would allow for better foraging efficiency of its members, as has been found recently in honeybees (Apis mellifera; Donaldson-Matasci et al 2013). Consequently, a tradeoff can be expected between intraspecific competition (Ashmole 1963, Furness andBirkhead 1984, Lewis et al 2001) and foraging facilitation in colonial seabirds.…”
Section: Discussionmentioning
confidence: 99%
“…Highly integrated colonies provide opportunities to examine the contribution of worker longevity, through its influence on colony size, to the emergence of cooperative group actions and collective decision-making. Larger groups are better able to average limited, individual information, improving the accuracy of collective decisions (Simons 2004) and efficiently solve problems (Morand-Ferron and Quinn 2011; Donaldson-Matasci et al 2013). Quorum rules can be rendered in large groups when only a few individuals have information (Couzin 2009), and larger groups can utilize a smaller proportion of informed individuals to arrive at a decision (Couzin et al 2005).…”
Section: Worker Longevity and Colony Fitnessmentioning
confidence: 99%
“…Surprisingly, these studies found that colonies would often not benefit from spatial communication [16][19]. For example, Donaldson-Matasci and Dornhaus [17] tested the effect of spatial communication in five different habitats, but found a positive effect of communication only in one.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, researchers took advantage of the fact that honeybees are unable to perform oriented dances on a horizontal comb with no or only diffuse light [16][19]. It is thus possible to create colonies with oriented (with spatial information; SI) or disoriented (no direction information; NI) dances and compare the foraging success of colonies in these two conditions.…”
Section: Introductionmentioning
confidence: 99%